Revolutionizing cleaning: The future of broomstick and dustpan design - Ricardo P Arciniega-Rocha; Vanessa C Erazo-Chamorro; Phetsalath Phimmavong; Szabo Gyula (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
In the context of increasing environmental awareness, the demand for sustainable products is on the rise. This research addresses the growing demand for sustainability by redesigning brooms and dustpans with eco-friendly materials, reducing waste and environmental impact. It emphasizes the goals of enhancing user experience, efficiency, durability, accessibility, and sustainability. A case study investigates the physical challenges faced by street sweepers and underscores the importance of anthropometric considerations in design. The resulting ergonomic redesign significantly reduces workload and musculoskeletal complaints, improving comfort and efficiency. The redesign introduces adjustable handles, lightweight materials, and a 3-in-1 brush system with eco-friendly components. The dustpan features an improved handle, an angled design for efficient debris collection, and a built-in cleaning comb. Both tools are constructed from lightweight yet durable materials and offer a foldable design for user convenience, emphasizing sustainability through eco-friendly materials. In conclusion, this holistic approach enhances the cleaning experience, promoting efficiency, user-friendliness, and environmental responsibility.